Krisis Kepercayaan Publik di Era Disinformasi Digital: Tantangan dan Strategi Penguatan Pelayanan Publik - Vivi Nilasari; Aldri Frinaldi; Nora Eka Putri; Asnil (Suria Academic Press, 2026)
The rapid development of digital technology has significantly transformed public service delivery while simultaneously increasing the spread of disinformation that may undermine public trust in government institutions. This study aims to analyze the impact of digital disinformation on public trust, identify the challenges faced by public services in the digital era, and formulate strategies for strengthening public trust. The study employs a qualitative approach using a library research method through the analysis of scientific articles, books, reports from international organizations, and relevant policy documents. The findings indicate that digital disinformation contributes to declining public trust by shaping negative perceptions of government performance and public service institutions. The main challenges include the widespread dissemination of false information, low levels of digital literacy, slow public communication responses, and the growing complexity of the digital information ecosystem. To address these challenges, integrated strategies are required, including enhancing information transparency, strengthening proactive public communication, improving digital literacy, utilizing digital technologies, and continuously improving public service quality. This study emphasizes that public trust is a fundamental element of effective public service delivery and must be reinforced through effective information governance in the era of digital disinformation.